Profile of Tuberculosis in Children and Adolescent at Dr. Soetomo General Hospital Surabaya - Litiya Parahita Putri Firnadi; Retno Asih Setyoningrum; Mohammad Yamin Sunaryo Suwandi (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2022)
Introduction: Tuberculosis is one of ten leading causes of death worldwide, including Indonesia. Indonesia is one of seven countries that causes 64% deaths due to tuberculosis. Tuberculosis is caused by Mycobacterium tuberculosis through droplet nuclei in the air. It can occur to any group age, including children and adolescent, if there is a contact history of people with tuberculosis infection. In 2016, one million children had tuberculosis and around 250,000 children died because of tuberculosis. This study aimed to know the profile of tuberculosis in children and adolescent at Dr. Soetomo General Hospital Surabaya.Methods: This was a descriptive study using retrospective approach. Sample of this study was collected from electronic medical record provided by Dr. Soetomo General Hospital Surabaya using statistic formula of single sample for estimated population proportions of children and adolescent with tuberculosis from 2013-2017, with total samples of 149 people.Results: There were 149 samples of children and adolescent patients with tuberculosis. Most of the children were mostly 0-4 years old and 57% were female. 84% of the children had been immunized with BCG and classified as moderate, and 35% were under nutritional status. This study showed that 67% of the children in household contacts of adult tuberculosis patients also had tuberculosis. The most frequent symptoms of tuberculosis in children and adolescent were fever (72%) and cough (80%).Conclusion: Tuberculosis in children and adolescent is more likely to occur in children than adolescent, especially children within group age of 0-4 years old. The number of pulmonary tuberculosis in children and adolescent are higher than extrapulmonary tuberculosis.